Konsep Geometri dalam Karya Seni Islam: Sebuah Tinjauan Literatur Sistematis - Chasanah, Arini Nur; Faradiba, Surya Sari (Mandalika Mathematics and Educations Journal, 2025)
This study aims to examine how geometric concepts are applied in Islamic artworks through a systematic literature review (SLR) approach. This study adopts five main steps from Khan's model, namely formulating research questions, identifying articles, generating quality, summarizing evidence, and interpreting findings. Of the 19 initial articles reviewed, only 4 articles met the inclusion and quality criteria. The analysis results show that geometric concepts such as isometry, symmetry, planementation, triangle congruence, and basic patterns (circle, triangle, and square) are widely used in Islamic artworks. The main findings are revealed in two major themes, namely: (1) geometry as an artistic structure and representation of spirituality, and (2) geometry as a medium for learning and cultural contextualization. This study confirms that geometric concepts not only beautify Islamic visual art, but also serve as a means of conveying the values of monotheism, cosmic order, and are effective educational media in contextual mathematics learning.